Metatranscriptomic analysis of lignocellulolytic microbial communities involved in high-solids decomposition of rice straw - Simmons, Christopher W (Biotechnol Biofuels, 2014)
BACKGROUND: New lignocellulolytic enzymes are needed that maintain optimal activity under the harsh conditions present during industrial enzymatic deconstruction of biomass, including high temperatures, the absence of free water, and the presence of inhibitors from the biomass. Enriching lignocellulolytic microbial communities under these conditions provides a source of microorganisms that may yield robust lignocellulolytic enzymes tolerant to the extreme conditions needed to improve the throughput and efficiency of biomass enzymatic deconstruction. Identification of promising enzymes from these systems is challenging due to complex substrate-enzyme interactions and requirements to assay for activity. In this study, metatranscriptomes from compost-derived microbial communities enriched on rice straw under thermophilic and mesophilic conditions were sequenced and analyzed to identify lignocellulolytic enzymes overexpressed under thermophilic conditions. To determine differential gene expression across mesophilic and thermophilic treatments, a method was developed which pooled gene expression by functional category, as indicated by Pfam annotations, since microbial communities performing similar tasks are likely to have overlapping functions even if they share no specific genes. RESULTS: Differential expression analysis identified enzymes from glycoside hydrolase family 48, carbohydrate binding module family 2, and carbohydrate binding module family 33 domains as significantly overexpressed in the thermophilic community. Overexpression of these protein families in the thermophilic community resulted from expression of a small number of genes not currently represented in any protein database. Genes in overexpressed protein families were predominantly expressed by a single Actinobacteria genus, Micromonospora. CONCLUSIONS: Coupling measurements of deconstructive activity with comparative analyses to identify overexpressed enzymes in lignocellulolytic communities provides a targeted approach for discovery of candidate enzymes for more efficient biomass deconstruction. Glycoside hydrolase family 48 cellulases and carbohydrate binding module family 33 polysaccharide monooxygenases with carbohydrate binding module family 2 domains may improve saccharification of lignocellulosic biomass under high-temperature and low moisture conditions relevant to industrial biofuel production.